2011
DOI: 10.1152/ajpcell.00496.2010
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition and function of red and white skeletal muscle mitochondria

Abstract: Glancy B, Balaban RS. Protein composition and function of red and white skeletal muscle mitochondria. Am J Physiol Cell Physiol 300: C1280 -C1290, 2011. First published February 2, 2011 doi:10.1152/ajpcell.00496.2010.-Red and white muscles are faced with very different energetic demands. However, it is unclear whether relative mitochondrial protein expression is different between muscle types. Mitochondria from red and white porcine skeletal muscle were isolated with a Percoll gradient. Differences in protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 55 publications
1
54
3
1
Order By: Relevance
“…Mitochondrial Percoll purification was carried out as previously described (Glancy and Balaban, 2011; Graham, 2001), with some modifications. Mitochondrial pellets (~5mgs) were resuspended in 1ml of sucrose wash buffer (250mM sucrose, 10mM HEPES (pH = 7.2), 0.1% BSA).…”
Section: Star ★ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial Percoll purification was carried out as previously described (Glancy and Balaban, 2011; Graham, 2001), with some modifications. Mitochondrial pellets (~5mgs) were resuspended in 1ml of sucrose wash buffer (250mM sucrose, 10mM HEPES (pH = 7.2), 0.1% BSA).…”
Section: Star ★ Methodsmentioning
confidence: 99%
“…Efforts to optimize the platform for new applications must consider several critical factors, including: a) tissue and cell type-specific differences in matrix dehydrogenase profiles, b) prioritization of substrate conditions when mitochondrial yield is limiting, and c) purity of tissue-specific mitochondrial isolations and potential need for sucrose- or Percoll-based purification protocols (Glancy and Balaban, 2011; Graham, 2001). To this point, it is noteworthy that the simple isolation protocol (without a sucrose-based buffer) used in the current work was sufficient to produce fractions with similar amounts of mitochondrial protein between tissues (Figures S4A and S4B).…”
Section: Star ★ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscles with more red muscle fibers (PM) will have more mitochondria and capillary density than muscles with more white fibers (LL). Hence TCA and glycolytic substrates will be utilized at different rates in red muscles than in white muscles (Kushmerick et al, 1992;Glancy and Balaban, 2011). Recently metabolomics was used to study color stability in ovine meat (Subbaraj et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…used two-dimensional gel electrophoresis and mass spectrometry to build a reference map of proteins and identified hundreds of distinct gene products including metabolic, transport, and contractile proteins [8]. Moreover, it was reported that the different energetic demands of white and red muscles were matched primarily by the different numbers of mitochondrial proteins in the two tissues [9]. Recently, a number of studies have focused on small non-coding RNAs, such as microRNAs (miRNAs) and small interfering RNAs (siRNAs), which are involved in the transcriptional and post-transcriptional regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%